Hubungan antara Komunikasi Interpersonal dengan Organizational Citizenship Behavior pada Karyawan Departemen Sumber Daya Manusia PT. Semen Padang - Herio Rizki Dewinda; Hidayatul Annisa (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to determine the relationship between interpersonal communication and organizational citizenship behavior in employees of the human resources department of PT. Semen Padang. The independent variable in this study is interpersonal communication and the dependent variable is organizational citizenship behavior. The measuring instrument used in this study is the scale of interpersonal communication and the scale of organizational citizenship behavior. The sampling technique in this study used a saturated sample technique. The sample in this study were 75 employees of the human resources department of PT Semen Padang. Validity and reliability test in this study usingtechnique Alpha Cronbach. The results of the validity coefficient on the scale of interpersonal communication ranged from rix= 0.323 to rix= 0.680 and reliability of α = 0.939 while on the OCB scale the value of the different power index values ranged from rix= 0.336 to rix= 0.833 with reliability coefficients amounting to α = 0.947. Based on data analysis, the correlation value of r= 0.455 is obtained with a significance level of 0.000, which means that the hypothesis is accepted. This shows that there is a significant relationship between interpersonal communication and organizational citizenship behavior in the human resources department of PT Semen Padang employees.